Bilateral high origin of terminal branches of brachial artery : A case report - Amitav Sarma; Bishwajeet Saikia (Wolters Kluwer Medknow Publications, 2014)
A case of bilateral high termination of brachial artery was found during a cadaveric dissection at NEIGRIHMS, Meghalaya. The brachial artery of both arms in the upper l/3rd divided into superficial and deep branches, the superficial artery was observed anteromedial and the deep artery posteromedial in relation to the median nerve. In the cubital fossa, the deep artery passed beneath the pronator teres muscle to give common interosseous artery which divided into anterior and posterior interosseous branches. The main trunk followed normal ulnar arterial course. In both the arms, the superficial branch of brachial artery remained lateral to the median nerve to reach the cubital fossa where it passed deep to the bicipital aponeurosis and descended just beneath the brachioradials muscle, following the normal course of radial artery. These developmental variations were thoroughly discussed and compared with previously published findings with their clinical importance.